Pathogenic Role of the CRL4 Ubiquitin Ligase in Human Disease - Zhou, Pengbo (Frontiers in Oncology, 2012)
The cullin 4-RING ubiquitin ligase (CRL4) family employs multiple DCAF (DDB1-CUL4 associated factors) substrate receptors to direct the degradation of proteins involved in a wide spectrum of cellular functions. Aberrant expression of the cullin 4A (CUL4A) gene is found in many tumor types, while mutations of the cullin 4B (CUL4B) gene are causally associated with human X-linked mental retardation. This focused review will summarize our current knowledge of the two CUL4 family members in the pathogenesis of human malignancy and neuronal disease, and discuss their potential as new targets for cancer prevention and therapeutic intervention.